KEMAMPUAN BERBAHASA ANAK AUTIS TIPE PDDNOS DI SLB MUHAMMADIYAH SIDAYU GRESIK: KAJIAN PSIKOLINGUISTIK - Yuli Fimawati; Ni Made Dhanawaty; Ni Wayan Sukarini (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2017)
Communication will be successful if the speakers and the hearers are successfully producing and comprehending the speech. In this case, if someone have difficulties to produced or understand the speech, they cannot communicate like a normal person, that is autism with PDDNOS. Autism with PDDNOS have differents characteristics with other types of autism, that is autism children with PDDNOS can communicate on social behaviour. The goals of this research are to know characteristics of language production based onScovel theory about language production of human. On the basis of the research problem, this study is a descriptive qualitative research, and the data is taken through observation with recording on videos. The data of this research is transfered to computer and it is observed several times, and then it is transcribed in order to be easily analyzed. Scovel’s theory (1998), is about language productionssuch as conceptialization, formulation, articulation, and self-monitoring. The result of this study is children with PDDNOS have difficulties to produced his language. He also repeated what the speaker says if he didnot understand the meaning of the communicaton.